Perancangan Standard Operating Procedure untuk Preventive Maintenance di Departemen Engineering : Studi Kasus - Christoforus Adhiatma Wibowo; Togar Wiliater Soaloon Panjaitan (Jurnal Titra, 2016)
Java Paragon Hotel and Residences is a hotel and apartment which located at Sura-baya. This project focused on designing of SOP and check sheet for preventive maintenance pro-gram. Background of this problem is the occurrence of multitasking and large number of staff that haven’t been trained well, so it needs a standard in doing preventive maintenance. Multi-tasking and the new employees occurred because of high turnover of ME Engineering. This pro-ject uses direct observation in the field and Q&A against the staff of Engineering Department. The results of the observations then organized into a SOP in the form of tables and is divided into 4 major activities, which are Checking, Cleaning, Lubrication, and Troubleshooting. Based on the existing SOP then it leads check sheet as a monitoring tools. Monitoring performed with purpose overseeing the implementation of preventive maintenance and the alignment with the existing SOP.